2005
DOI: 10.1001/archsurg.140.9.902
|View full text |Cite
|
Sign up to set email alerts
|

Suicide

Abstract: Hypothesis:We hypothesized that a significant number of injuries and deaths due to suicide occurred in patients undergoing psychiatric treatment. Design:We performed a retrospective cohort study of patients who committed suicide and patients with intentional self-inflicted injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Figure 5 indicates that 60% of the GGB victims had a known psychiatric disorder, similar to some previous reports (Schecter, Klassen, O’Connor, Potts, & Ochitill, 2005) but lower than others (Beautrais et al, 1996; Fleischmann, Bertolote, Belfer, & Beautrais, 2005). When compared by age groups, psychiatric factors exceed both the nonpsychiatric and unknown factors in nearly every age group.…”
Section: Resultssupporting
confidence: 87%
“…Figure 5 indicates that 60% of the GGB victims had a known psychiatric disorder, similar to some previous reports (Schecter, Klassen, O’Connor, Potts, & Ochitill, 2005) but lower than others (Beautrais et al, 1996; Fleischmann, Bertolote, Belfer, & Beautrais, 2005). When compared by age groups, psychiatric factors exceed both the nonpsychiatric and unknown factors in nearly every age group.…”
Section: Resultssupporting
confidence: 87%
“… 18 19 Poor mental health is also a risk factor for non-accidental injuries. 20 21 The impact of mental health following injury within Burkina Faso among general older adult population has not been studied, with mental health studies limited to vulnerable populations such as sex workers and children exposed to physical violence in Burkina Faso. 22 23 …”
Section: Introductionmentioning
confidence: 99%
“…Attempted suicide remains as an unmet challenge of the trauma system because of the lack of documentation, countless potential mechanisms of injury, and difficulties in capturing suicidal behavior. [ 6 ] The main risk factors for suicide attempts are young age; socioeconomic status; unemployment; mental disorders such as bipolar disorders, depression, and schizophrenia; drug use and alcohol; history of prior attempts, family history of suicide, assault, and head injuries. [ 6 7 8 ] In addition, not living at home is another risk factor for repeat attempts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] The main risk factors for suicide attempts are young age; socioeconomic status; unemployment; mental disorders such as bipolar disorders, depression, and schizophrenia; drug use and alcohol; history of prior attempts, family history of suicide, assault, and head injuries. [ 6 7 8 ] In addition, not living at home is another risk factor for repeat attempts. [ 7 ] The World Health Organization (WHO) reported that the number of suicide attempts exceed the completed suicide by up to 20 times.…”
Section: Introductionmentioning
confidence: 99%